Peningkatan Hasil Belajar Siswa dengan Penerapan Model Pembelajaran Direct Instruction - Denisa Safitri; Sukardi Sukardi (Departement of Electrical Engineering Universitas Negeri Padang, 2025)
Abstract - The low learning outcmes of students in the Electrical Motor Installlation subject at SMK Negeri 1 Rengat Barat indicate the need for a more effective model. This study aims to improve student’s learning outcomes through the implementation off the Direct Instruction learning model. The research employed a uantitative approach with an experimental method using One Group Pretest-Posttest design. The subjects were 28 student of grade XI Elektrical Power Engineering in the 2024/2025 academic year. Data were collection through pretest and posttest instruments and analyzed using the T-Test, N-Gain Score and Efect Size. The results shoed a significant improvement in student’s learning outcomes,with an average posttest score 81,29 compared to pretest score of 53.14. the N-Gain alue of 0.60 indicated moderate improvement, while the learning mastery level reached 96% with a high effect size. Based on these resuld, the Direct Instruction learning model proved effective in improving student’s learning outcomes and fostering their active engagement in the learning process. Therefore, this model can sarve as alternative instruction strategy relevant to vocational subject in vocation high schools.